PERBEDAAN RESISTENSI CYCLIC FATIGUE FRACTURE DUA JENIS HEAT TREATED ROTARY FILES - Iskandar, Mochammad Marshalldanard A.; Melaniwati; Pratiwi, Deviyanti (E-Prodenta Journal of Dentistry, 2025)
Background: NiTi rotary file is an instrument that famous for its flexible and strong properties. Instrument fracture during preparation due to cyclic fatigue is one of the main causes of rotary file fracture. The geometric shape of a rotary file will determine its resistance properties because it is in direct contact with the root canal wall and will determine its resistance to cyclic fatigue. Objective: This study aims to determine the difference in cyclic fatigue fracture resistance of two heat treated rotary files that have different geometric shape. Methods: The research inserted rotary files with an endomotor operating at 400 rpm and 2.0 torque into artificial stainless steel root canals with a 90-degree curvature and 2 mm diameter, treated with 5.25% NaOCl. It included two groups (flat design and S-Shape), each with 5 samples, and measured the duration of each sample using a stopwatch. Results: This research show that there is a significant difference in time (p<0.05). Conclusion: The flat design rotary file shows stronger resistance to cyclic fatigue fracture compared to the S-Shape rotary file.